Biliary stent with self-degrading coating and method of making

CN122912195APending Publication Date: 2026-10-16SUZHOU BONTES MATERIAL TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611418716.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-14
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

但是,现有的载药覆膜支架其核心关注点仅在于如何通过涂层释放“雷帕霉素”或“紫杉醇”等抗增殖药物来抑制血管平滑肌增生,从未有技术将该成熟的控释覆膜工艺用于包裹生物酶,更未有研究尝试利用覆膜释放出的酶来加速催化支架基体本身的水解

Benefits of technology

本发明的制备方法结合了成熟的支架制造工艺,首先通过螺杆挤出和吹塑工艺将聚乳酸加工成特定尺寸的管材,再利用精密激光雕刻机雕刻出网格状胆管支架基体,最后通过成熟的载药支架涂覆工艺完成蛋白酶K的负载,通过负载猪胰腺蛋白酶K,成功实现了聚乳酸胆管支架的高效、均匀加速降解,达到了预期的临床引流及按期自行降解清除的设计目的。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912195A_ABST
    Figure CN122912195A_ABST
Patent Text Reader

Abstract

The application discloses a bile duct stent with a self-adaptive degradation coating and a preparation method thereof, and belongs to the technical field of biomedical polymer materials and medical devices. The bile duct stent comprises a stent base made of a biodegradable polyester material, and a biological enzyme for promoting polyester degradation loaded on the surface or inside of the stent base. The preparation method of the application extrudes the polyester material into a pipe material through a screw, processes a grid structure stent base through precise laser engraving, and then loads the biological enzyme on the stent by using a stent drug loading coating process. The application utilizes the specific catalytic hydrolysis of the biological enzyme on the polyester material, significantly improves the degradation rate of the polyester bile duct stent in the body and in the bile environment, and realizes the uniform and controllable degradation of the stent. The application fundamentally avoids the clinical problems caused by the slow or uneven in-vivo degradation of the traditional degradable stent, such as bile sludge deposition, premature occlusion or fracture displacement of the stent, and has a high clinical application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biomedical polymer materials and medical device manufacturing technology, specifically to a bile duct stent with an adaptive degradation coating and its preparation method. Background Technology

[0002] Bile duct stricture and biliary obstruction are common and intractable diseases in digestive surgery, and stent implantation is often used clinically to restore bile drainage. Traditional metal stents, due to their non-degradability, are prone to tissue granulation and restenosis with long-term placement. Tubular sculpted stents made of biodegradable polyester materials such as polylactic acid (PLA) have become the main alternative due to their excellent biocompatibility. However, the harmless degradation of ordinary PLA materials in vivo relies entirely on extremely slow autocatalytic hydrolysis, and the loss of overall strength and mass usually takes more than a year. The biliary system has a unique environment; bile is rich in easily precipitated components such as bilirubin and cholesterol. The surface of a stent that degrades too slowly is prone to sand-like deposits under long-term bile erosion, leading to premature blockage of the stent lumen.

[0003] To overcome the drawback of traditional polylactic acid (PLA) degradation, which relies entirely on in vivo autocatalytic hydrolysis and results in an excessively long degradation cycle (typically over a year), the technology of accelerating polyester hydrolysis by catalyzing ester bond breakage with specific bio-enzymes has become a research hotspot in recent years. Currently, researchers both domestically and internationally have made significant progress in the process design and mechanism of enzymatic PLA degradation.

[0004] In the field of material composite modification and blending, US Patent US11198767B2 (corresponding to international application WO2016198652A1) discloses a method of directly compounding and extruding a polyester matrix with lipase or protease as a degradation component in a molten state. This method adjusts the microenvironment pH by introducing mineral acid-resistant fillers such as carbonates and talc, achieving efficient depolymerization of the high molecular weight polylactic acid backbone under mild conditions. However, for precision laser-engraved medical scaffolds with high geometric accuracy and mechanical requirements, ordinary enzymes cannot achieve deep degradation because they cannot break through the dense crystalline lattice of the polymer. To address this challenge, international patent application WO2024076959A1 reports a new technology for the enzymatic degradation of crystallizable polymers. This technology involves subjecting highly crystalline polylactic acid to specific physical or chemical pretreatment conditions to disrupt the crystalline lattice backbone, allowing biological enzymes to penetrate and attack the ester bonds within the crystalline regions, achieving deep enzymatic stripping and efficient hydrolysis of highly crystalline polyester from the surface to the interior.

[0005] Although the aforementioned existing technologies strongly demonstrate that enzymatic hydrolysis of polylactic acid can significantly shorten its degradation cycle, existing industrial methods tend to cause the material to collapse and disintegrate rapidly as a whole, lacking precise balance control over the early high radial support performance and later specific window period clearance of Class III implantable medical devices.

[0006] Parallel to this development is the increasingly mature surface coating technology for drug-eluting stents. For example, US Patent 20060246108A1 details a method for constructing a drug-controlled release coating on the surface of a biodegradable polymer stent. This method utilizes polymer matrices such as polylactic-coated glycolic acid (PLGA) as a carrier to encapsulate and coat small-molecule drugs onto the stent surface, achieving uniform, long-term, and slow release of the active ingredient. This type of surface coating process not only effectively maintains the physical morphology of the encapsulated material but also allows for precise control of release kinetics by adjusting the carrier ratio. However, the core focus of existing drug-eluting stents is solely on how to release antiproliferative drugs such as rapamycin or paclitaxel through the coating to inhibit vascular smooth muscle proliferation. No technology has ever used this mature controlled-release coating process to encapsulate biological enzymes, nor has any research attempted to utilize the enzymes released from the coating to accelerate the hydrolysis of the stent matrix itself.

[0007] In conclusion, if, while maintaining the initial high radial support of the polylactic acid (PLA) bile duct stent, existing mature drug-eluting stent coating controlled-release technology can be used to safely immobilize highly active lipases on the stent surface, thereby achieving efficient and uniform accelerated degradation of the stent from the surface inwards, it is expected to overcome the application bottleneck of biodegradable bile duct stents. This could ultimately solve the intractable clinical problem of bile stasis and obstruction.

[0008] Therefore, it is essential to design a bile duct stent with an adaptive degradation coating and its preparation method. Summary of the Invention

[0009] The purpose of this invention is to provide a bile duct stent with an adaptive degradation coating and a method for preparing the same, so as to solve the problems mentioned in the background art.

[0010] To solve the above-mentioned technical problems, the present invention provides the following technical solution: A bile duct stent with an adaptive degradation coating includes: a stent matrix made of a biodegradable polylactic acid material; and a bioenzyme loaded on the surface of the stent matrix.

[0011] As a preferred embodiment, the polylactic acid material includes polylactic acid (PLLA), polylactic acid-glycolic acid copolymer (PLGA), etc., with a weight-average molecular weight of 10,000 to 500,000 Da, a crystallinity controlled at 10% to 60%, preferably 30% to 50%, and a tensile strength ≥120 MPa, in order to balance the initial mechanical strength and the basic degradation rate.

[0012] The bioenzyme is loaded onto the scaffold via one or a combination of the following two methods: Coating encapsulation: The bioenzyme is dissolved in a biodegradable polymer carrier to form a slow-release coating on the scaffold surface. Chemical coupling / physical adsorption: After chemical activation, the bioenzyme is immobilized by covalent bonds on the scaffold surface.

[0013] Compared with the prior art, the beneficial effects achieved by the present invention are: The preparation method of this invention combines mature stent manufacturing technology. First, polylactic acid is processed into tubes of specific sizes through screw extrusion and blow molding. Then, a grid-like bile duct stent matrix is ​​engraved using a precision laser engraving machine. Finally, proteinase K is loaded through a mature drug-eluting stent coating process. By loading porcine pancreatic proteinase K, the efficient, uniform, and accelerated degradation of the polylactic acid bile duct stent is successfully achieved, realizing the intended design purpose of clinical drainage and timely self-degradation and clearance. Attached Figure Description

[0014] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used in conjunction with embodiments of the invention to explain the invention and do not constitute a limitation thereof. In the drawings: Figure 1 This is a diagram of the final support structure obtained in this invention; Figure 2 This is a schematic diagram of proteinase K coated on the surface of a scaffold. Detailed Implementation

[0015] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0016] Example 1 See Figure 1-2 L-polylactic acid (PLLA) granules with a weight average molecular weight of 150,000 Da were taken, dried thoroughly in a drying oven, and fed into a single-screw extruder for precision extrusion at 190°C to form pipes with an outer diameter of 1.8 mm and an inner diameter of 0.5 mm.

[0017] The aforementioned tubing was blow-molded at 120°C into polylactic acid tubing with an outer diameter of 3.3 mm and an inner diameter of 3.05 mm. The tubing was then placed in a precision laser cutting machine and laser-engraved according to a preset bile duct stent grid pattern to obtain the engraved polylactic acid bile duct stent substrate.

[0018] Weigh 50-200 mg of PLGA (LA / GA=50:50) and dissolve it in 5 mL of dichloromethane. Separately weigh 5-10 mg of porcine pancreatic proteinase K powder (activity approximately 100 U / mg) and suspend it in the above solution. Sonicate the solution to disperse it evenly and prepare an enzyme-coated solution.

[0019] Using a micro-precision sprayer, the enzyme-loaded coating solution was uniformly sprayed onto the outer surface and inner wall of the polylactic acid bile duct stent substrate. The substrate was then vacuum-dried at 4°C for 24 hours to remove residual solvent, yielding the target enzyme-loaded bile duct stent. The porcine pancreatic proteinase K loading on the stent surface was measured to be approximately 1–2 mg / cm³. 2 .

[0020] Example 2 The polylactic acid bile duct stent matrix was manufactured according to the method of Example 1.

[0021] The scaffold matrix was immersed in a 0.1 mol / L sodium hydroxide solution for 5 minutes to generate some carboxyl and hydroxyl groups on its surface. It was then activated at room temperature for 30 minutes with an aqueous solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDC) and N-hydroxysuccinimide (NHS).

[0022] After washing the activated scaffold, it was immediately immersed in a phosphate buffer solution (pH 7.4) containing 2 mg / mL porcine pancreatic proteinase K and covalently bound at 4°C for 12 hours. After removal, it was rinsed with deionized water and freeze-dried to obtain a bile duct scaffold with porcine pancreatic proteinase K covalently immobilized on its surface.

[0023] Comparative Example 1 Polylactic acid bile duct stents were manufactured using the same process as in Example 1, but porcine pancreatic proteinase K was not added in the coating preparation in step 2; only pure PLGA solution was sprayed.

[0024] Effect verification experiment The supports from Examples 1, 2, and Comparative Example 1 were placed in fresh human bile at a constant temperature of 37°C for isothermal degradation experiments, with the degradation solution being replaced every two weeks. Molecular weight change: At week 4 after implantation, the molecular weight of PLLA in Comparative Example 1 (without enzyme) decreased by only about 5%; while the molecular weight of the scaffolds in Example 1 and Example 2 decreased by 35% and 28% respectively, showing a significant enzymatic accelerated degradation effect.

[0025] Mass loss and weight loss rate: By week 12, the stent of Comparative Example 1 had basically no change in shape, and the inner surface of the lumen began to become rough due to the adhesion of bile components; while the stent of Example 1 had undergone uniform degradation and thinning, with a weight loss rate of more than 60%, and the surface was smooth with no obvious sediment deposits.

[0026] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.

[0027] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A bile duct stent with an adaptive degradation coating, characterized in that, include: Scaffold matrix: The scaffold matrix is ​​made of biodegradable polyester material; Bioenzyme: The bioenzyme is coated on the surface of the scaffold substrate, and the bioenzyme coating accelerates the degradation of the polyester material through an enzymatic hydrolysis reaction.

2. The bile duct stent with an adaptive degradation coating according to claim 1, characterized in that, The biodegradable polyester material includes one or more of poly(L-lactic acid), poly(D-lactic acid), poly(racemic lactic acid), polylactic acid-glycolic acid copolymer, polylactic acid-ethylene glycol copolymer, and polycaprolactone. The biodegradable polyester material has a weight-average molecular weight of 60,000 to 300,000 Da, a crystallinity of 10% to 50%, and a tensile strength ≥120 MPa.

3. A bile duct stent with an adaptive degradation coating according to claim 1, characterized in that, The bioenzyme is one or more of the protease and lipase that have good degradation activity against polyester. The bioenzyme is proteinase K, which is derived from the pancreas of mammals, microorganisms, or plants; The proteinase K is one or more of porcine trypsin K, Candida albicans proteinase K, or Rhizopus proteinase K.

4. A bile duct stent with an adaptive degradation coating according to claim 1, characterized in that, The bio-enzyme is loaded onto the scaffold matrix by at least one of the following methods: Method 1: The bio-enzyme is encapsulated in a biodegradable polymer carrier and coated onto the surface of the scaffold matrix in the form of a coating; Method 2: The surface of the scaffold substrate is modified with hydrophilic or chemical activation, so that the biological enzyme is fixed to the surface of the scaffold substrate through covalent bonding or physical adsorption.

5. A bile duct stent with an adaptive degradation coating according to claim 4, characterized in that, The biodegradable polymer carrier in Method 1 includes one or more of polylactic acid-glycolic acid copolymer, polycaprolactone, polyethylene glycol, or chitosan. The proteinase K loading in the coating is 0.1~10 mg / cm³. 2 The enzyme activity is 10~500 U / cm 2 .

6. A method for preparing a bile duct stent with an adaptive degradation coating as described in any one of claims 1-5, characterized in that, Includes the following steps: S1: Biodegradable polyester material is fed into a screw extruder and extruded to obtain polylactic acid pipes; S2: Perform precision laser engraving on the polylactic acid tubing to process a support substrate with a specific mesh structure; S3: Using a drug-eluting stent fabrication process, proteinase K is loaded onto the stent substrate to obtain a bile duct stent with an adaptive degradation coating.

7. The method for preparing a bile duct stent with an adaptive degradation coating according to claim 6, characterized in that, Step S3 is as follows: A coating solution is prepared by dissolving or suspending proteinase K and a biodegradable polymer carrier in a solvent, wherein the solvent is an organic solvent or an aqueous system. The coating solution is uniformly coated onto the surface of the scaffold substrate using spraying, dipping, or dot coating methods, and then dried to remove the solvent, forming a controlled-release degradation coating loaded with proteinase K.

8. The method for preparing a bile duct stent with an adaptive degradation coating according to claim 7, characterized in that, The organic solvent includes one or more of dichloromethane, trichloromethane, ethyl acetate, acetone, or ethanol; The organic solvent is selected from ICH Class III solvents that are low in toxicity and harmless to the human body, including one or more of ethyl acetate, acetone or ethanol; In the coating solution, the mass ratio of the bio-enzyme to the biodegradable polymer carrier is 1:5 to 1:

50.

9. A method for preparing a bile duct stent with an adaptive degradation coating according to claim 6, characterized in that, Between steps S2 and S3, the scaffold substrate may also undergo heat treatment, chemical activation, or plasma surface modification.

10. The use of a biodegradable bile duct stent according to any one of claims 1-5 in a medical device for treating biliary stricture, bile duct injury or cholestasis.

Citation Information

Patent Citations

  • Process for preparing a biodegradable plastic composition

    US11198767B2

  • Amorphous poly(D,L-lactide) coating

    US20060246108A1

  • Biodegradable polyester composition and uses thereof

    WO2016198652A1

  • Enzymatic degradation of crystallizable polymers or copolymers and post-consumer / post-industrial polymeric materials containing crystallizable polymers or copolymers

    WO2024076959A1